Amount of Learning and Signal Stability Modulate Emergence of Structure and Iconicity in Novel Signaling Systems. Issue 11 (10th November 2021) - Kempe, Vera; Gauvrit, Nicolas; Panayotov, Nikolay; Cunningham, Sheila; Tamariz, Monica
Abstract: Iterated language learning experiments that explore the emergence of linguistic structure in the laboratory vary considerably in methodological implementation, limiting the generalizability of findings. Most studies also restrict themselves to exploring the emergence of combinatorial and compositional structure in isolation. Here, we use a novel signal space comprising binary auditory and visual sequences and manipulate the amount of learning and temporal stability of these signals. Participants had to learn signals for meanings differing in size, shape, and brightness; their productions in the test phase were transmitted to the next participant. Across transmission chains of 10 generations each, Experiment 1 varied how much learning of auditory signals took place, and Experiment 2 varied temporal stability of visual signals. We found that combinatorial structure emerged only for auditory signals, and iconicity emerged when the amount of learning was reduced, as an opportunity for rote‐memorization hampers the exploration of the iconic affordances of the signal space. In addition, compositionality followed an inverted u‐shaped trajectory raising across several generations before declining again toward the end of the transmission chains. This suggests that detection of systematic form‐meaning linkages requires stable combinatorial units that can guide learners toward the structural properties of signals, but these combinatorial units had not yet emerged in these unfamiliar systems. Our findings underscore the importance of systematically manipulating training conditions and signal characteristics in iterated language learning experiments to study the interactions between the emergence of iconicity, combinatorial and compositional structure in novel signaling systems.